tPA Deficiency in Mice Leads to Rearrangement in the Cerebrovascular Tree and Cerebroventricular Malformations - Stefanitsch, Christina; Lawrence, Anna-Lisa E.; Olverling, Anna; Nilsson, Ingrid; Fredriksson, Linda (Frontiers in Cellular Neuroscience, 2015)
The serine protease tissue-type plasminogen activator (tPA) is used as a thrombolytic agent in the management of ischemic stroke, but concerns for hemorrhagic conversion greatly limits the number of patients that receive this treatment. It has been suggested that the bleeding complications associated with thrombolytic tPA may be due to unanticipated roles of tPA in the brain. Recent work has suggested tPA regulation of neurovascular barrier integrity, mediated via platelet derived growth factor (PDGF)-C/ PDGF receptor-α (PDGFRα) signaling, as a possible molecular mechanism affecting the outcome of stroke. To better understand the role of tPA in neurovascular regulation we conducted a detailed analysis of the cerebrovasculature in brains from adult tPA deficient (tPA-/-) mice. Our analysis demonstrates that life-long deficiency of tPA is associated with rearrangements in the cerebrovascular tree, including a reduction in the number of vascular smooth-muscle cell covered, large diameter, vessels and a decrease in vessel-associated PDGFRα expression as compared to wild-type littermate controls. In addition, we found that ablation of tPA results in an increased number of ERG (ETS related gene) positive endothelial cells and increased junctional localization of the tight junction protein ZO1. This is intriguing since ERG is an endothelial transcription factor implicated in regulation of vascular integrity. Based on these results we propose that the protection of barrier properties seen utilizing these tPA-/- mice might be due, at least in part, to these cerebrovascular rearrangements. In addition, we found that tPA-/- mice displayed mild cerebral ventricular malformations, a feature previously associated with ablation of PDGF-C, thereby providing an in vivo link between tPA and PDGF signaling in CNS development. Taken together, the data presented here will advance our understanding of the role of tPA within the CNS and in regulation of cerebrovascular permeability.